Analisis Modal Bank Syariah Setelah Konversi (Studi Kasus Bank Aceh Syariah) - Nadzilla, Siti Sonya; Mahendra, Oriza (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
On September 1, 2016, PT Bank Aceh Syariah transformed from a conventional bank to a Sharia bank with permission from the Board of Commissioners of the Financial Services Authority (OJK) under Number KEP-44/D.03/2016. The capital from the conventional system was converted into the capital of the Sharia bank, with the ownership of shares being regulated by a percentage-based formula. The parent Sharia bank holds the largest portion of shares, while the conventional bank retains some shares. The significant differences between the conventional and Sharia banking systems were considered incompatible with the principles and mechanisms of Sharia banking, as legal questions could arise when they are operated simultaneously from an Islamic perspective This research aims to determine the status of the capital of Bank Aceh Syariah after its conversion from the perspective of Islamic law This study employs a qualitative approach with a descriptive method. The qualitative approach involves gathering data in a natural environment with the goal of interpreting occurring phenomena. Bank Aceh Syariah has an important composition of capital sources for continuity and operational performance. Funds from the Aceh government are the main source, reflecting support for sharia banking in this region. Capital also comes from loans and internal bank capital, all of which form an integral financial foundation